Membangkitkan Suatu Matriks Unimodular Dengan Python - Arifin, Samsul; Muktyas, Indra Bayu (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
An SPL can be represented as a multiplication of the coefficient matrix and solution vector of the SPL. Determining the solution of an SPL can use the inverse matrix method and Cramer's rule, where both can use the concept of the determinant of a matrix. If the coefficient matrix is a unimodular matrix, then all solutions of an SPL are integers. In this paper we will present a method of generating a unimodular matrix using Python so that it can be utilized on an SPL.Â Keywords: SPL, Unimodular Matrix, Python